2015
DOI: 10.1016/j.ajog.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of a validated prediction model for in vitro fertilization: comparison of live birth rates and multiple birth rates with 1 embryo transferred over 2 cycles vs 2 embryos in 1 cycle

Abstract: Objective To use a validated prediction model to examine whether single embryo transfer (SET) over two cycles results in live birth rates (LBR) comparable to two embryos transferred (DET) in one cycle, while reducing the probability of a multiple birth (i.e., multiple birth rate, MBR). Study Design Prediction models of LBR and MBR for a woman considering ART developed from linked cycles from the Society for Assisted Reproductive Technology Clinic Outcome Reporting System (SART CORS) for 2006-2012 was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…These results align with other studies that have found cumulative live birth rates for two SETs to be at least as high as live birth rates for one DET (1618) and two SETs to be more cost effective than one DET (1921). These studies were small in size compared with our study or did not explore both birth rates and costs.…”
Section: Discussionsupporting
confidence: 91%
“…These results align with other studies that have found cumulative live birth rates for two SETs to be at least as high as live birth rates for one DET (1618) and two SETs to be more cost effective than one DET (1921). These studies were small in size compared with our study or did not explore both birth rates and costs.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, some studies have reported that two sequential SET have a similar cumulative LBR with DET. Additionally, two sequential SET had lower MPR and cost than DET . Although our study did not include data from two sequential SET, the IR were similar between GG and GS.…”
Section: Discussionmentioning
confidence: 82%
“…To evaluate the optimal number of embryos to transfer, several studies compared single blastocyst transfer (SBT) to double blastocyst transfer (DBT). [7][8][9][10][11] According to these studies, DBT are associated with a higher live birth rate (LBR) than SBT. However, the multiple pregnancy rate (MPR) is significantly lower with SBT.…”
Section: Introductionmentioning
confidence: 99%
“…Even more astonishing than the aforementioned data is the finding that only around 20% of multiple gestations occur with natural conception [27]. The results of a very recent study showed even more reason to choose SET: an ART treatment of two cycles of SET results in comparable pregnancy rates to that of one cycle of DET, while concurrently causing a drop in multiple pregnancy rates by more than 90% [28]. As indicated, a decline in twinning rate following SET or DET is feasible without a drop in overall pregnancy and live-birth rates by, when given the choice, opting for SET instead of DET.…”
Section: Set Versus Det and Met Multiple Pregnancy And Metmentioning
confidence: 88%